Existence and attractivity results for Hilfer fractional differential equations - Abbas, S.; Benchohra, M.; Henderson, J. (Нелінійні коливання, 2018)
We present some results of the existence of attracting solutions of some fractional differential equations of Hilfer type. The results of the existence of solutions are applied to the Schauder fixed point theorem. We prove that all solutions are uniformly locally attracting.